Learn more about

Refine search

Results (displaying matches 1-50 of 1926) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
587.a.587.1 587.a \(y^2 + (x^3 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ 1
932.a.3728.1 932.a \(y^2 + y = x^6 - 2x^5 + x^4 + x^2 - x\) $\mathrm{USp}(4)$ 1
1497.b.13473.1 1497.b \(y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - x^2\) $\mathrm{USp}(4)$ 1
1503.a.4509.1 1503.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 3x^3 + x\) $\mathrm{USp}(4)$ 1
1575.a.165375.1 1575.a \(y^2 + (x^2 + x + 1)y = -x^5 + 2x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 1
1854.a.11124.1 1854.a \(y^2 + (x^3 + x^2 + x)y = -2x^3 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ 1
2304.a.13824.1 2304.a \(y^2 + y = 2x^5 + 3x^4 - x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
2336.a.37376.1 2336.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^4 - 3x^3 + x\) $\mathrm{USp}(4)$ 1
2457.a.154791.1 2457.a \(y^2 + (x^3 + 1)y = x^5 - 3x^3 - x^2 + 2\) $\mathrm{USp}(4)$ 1
2556.a.30672.1 2556.a \(y^2 + x^3y = -2x^4 - 2x^3 + x^2 + 2x + 1\) $\mathrm{USp}(4)$ 1
2588.a.82816.1 2588.a \(y^2 + (x^3 + 1)y = x^3 + 2x^2\) $\mathrm{USp}(4)$ 1
2672.a.342016.1 2672.a \(y^2 + y = x^6 - 6x^4 - 7x^3 - x^2 + x\) $\mathrm{USp}(4)$ 1
2848.a.45568.1 2848.a \(y^2 + y = x^6 - 2x^5 - 7x^4 - 5x^3 + x\) $\mathrm{USp}(4)$ 1
2952.a.283392.1 2952.a \(y^2 + x^3y = -2x^4 - x^3 + 3x^2 + 4x + 4\) $\mathrm{USp}(4)$ 1
2980.a.381440.1 2980.a \(y^2 + (x^3 + 1)y = 2x^5 + 3x^4 - x^2 - x\) $\mathrm{USp}(4)$ 1
3092.a.98944.1 3092.a \(y^2 + (x^3 + 1)y = -x^4 + 3x^2 + x\) $\mathrm{USp}(4)$ 1
3138.a.301248.1 3138.a \(y^2 + (x^3 + x)y = -x^4 - 2x^2 - x + 1\) $\mathrm{USp}(4)$ 1
3462.a.560844.1 3462.a \(y^2 + (x + 1)y = x^5 - 3x^3 + 4x^2 - 3x\) $\mathrm{USp}(4)$ 1
3528.b.338688.1 3528.b \(y^2 + (x^3 + x^2 + x + 1)y = 2x^4 - x^3 - x\) $\mathrm{USp}(4)$ 1
3564.b.705672.1 3564.b \(y^2 + (x^3 + x + 1)y = 2x^2 + 4x + 2\) $\mathrm{USp}(4)$ 1
3798.a.729216.1 3798.a \(y^2 + (x + 1)y = x^6 + x^5 + 2x^4 - x^2\) $\mathrm{USp}(4)$ 1
3812.a.243968.1 3812.a \(y^2 + (x^3 + 1)y = 2x^2 - 2x\) $\mathrm{USp}(4)$ 1
4128.b.594432.1 4128.b \(y^2 + y = x^6 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 1
4388.a.140416.1 4388.a \(y^2 + (x^3 + 1)y = -x^5 + 2x^2 - x\) $\mathrm{USp}(4)$ 1
4400.b.352000.1 4400.b \(y^2 = x^6 - 2x^4 - 3x^3 + x^2 + 3x + 1\) $G_{3,3}$ 1
4428.a.239112.1 4428.a \(y^2 + (x^3 + x + 1)y = -2x^5 - x^4 - x\) $\mathrm{USp}(4)$ 1
4489.a.4489.1 4489.a \(y^2 + (x^3 + x + 1)y = x^5 - x\) $G_{3,3}$ 2
5008.a.641024.1 5008.a \(y^2 + (x^3 + x)y = x^5 - x^4 - 2x^3 + x + 1\) $\mathrm{USp}(4)$ 1
5026.a.35182.1 5026.a \(y^2 + (x^3 + 1)y = 4x^5 + 22x^4 + 46x^3 + 28x^2 + 5x\) $\mathrm{USp}(4)$ 2
5280.a.633600.1 5280.a \(y^2 + (x^2 + 1)y = x^5 + 12x^4 + 5x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 1
5329.b.5329.1 5329.b \(y^2 + (x^3 + x^2 + 1)y = x^3 - x\) $G_{3,3}$ 2
5360.a.686080.1 5360.a \(y^2 + (x^3 + x)y = x^4 - x^3 - 2x^2 + x + 1\) $\mathrm{USp}(4)$ 1
5364.a.193104.1 5364.a \(y^2 + (x^3 + x)y = 2x^3 + 3x^2 + 2x + 1\) $\mathrm{USp}(4)$ 1
5464.a.349696.1 5464.a \(y^2 + (x + 1)y = x^6 + 2x^5 + x^4 - x^3\) $\mathrm{USp}(4)$ 1
5580.a.33480.1 5580.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - 2x^3 + x^2\) $\mathrm{USp}(4)$ 1
5904.a.70848.1 5904.a \(y^2 + (x^3 + x^2 + x + 1)y = -2x^2 - 2x\) $\mathrm{USp}(4)$ 1
6210.c.894240.1 6210.c \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + 4x^2 - 5x + 1\) $\mathrm{USp}(4)$ 1
6336.a.152064.1 6336.a \(y^2 + (x^3 + x)y = -x^4 - 2x^3 + 2x + 1\) $\mathrm{USp}(4)$ 1
6437.a.6437.1 6437.a \(y^2 + (x^3 + x^2 + x + 1)y = x^3 - 2x\) $\mathrm{USp}(4)$ 2
6845.a.6845.1 6845.a \(y^2 + x^3y = x^5 - 7x^3 - 16x^2 - 15x - 5\) $G_{3,3}$ 2
7200.d.345600.1 7200.d \(y^2 + y = x^6 - 2x^4 - x^3 + 4x^2 - 2x\) $\mathrm{USp}(4)$ 1
7440.b.89280.1 7440.b \(y^2 + y = 2x^5 + x^4 - 2x^3 + x\) $\mathrm{USp}(4)$ 1
7529.a.7529.1 7529.a \(y^2 + (x^3 + x^2 + x)y = x^2 + 2x + 1\) $\mathrm{USp}(4)$ 2
7549.a.7549.1 7549.a \(y^2 + (x^3 + x + 1)y = -2x^4 + 3x^2 - x - 2\) $\mathrm{USp}(4)$ 2
7609.a.7609.1 7609.a \(y^2 + (x^3 + x + 1)y = x^2 - x\) $\mathrm{USp}(4)$ 2
7643.a.7643.1 7643.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ 2
7697.a.7697.1 7697.a \(y^2 + (x^3 + 1)y = x^3 - x^2\) $\mathrm{USp}(4)$ 2
7848.a.188352.1 7848.a \(y^2 + (x^3 + x)y = x^5 - x^2 - x + 1\) $\mathrm{USp}(4)$ 1
7927.b.7927.1 7927.b \(y^2 + x^3y = -2x^4 - x^3 + 3x^2 + x - 1\) $\mathrm{USp}(4)$ 2
8100.a.145800.1 8100.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 - 4x^2 - 2x + 2\) $\mathrm{USp}(4)$ 1
Next

Download all search results for